(NmUZYKAL_NAQ LITERATURA DLQ (B4 (NKLASSA DETSKOJ MUZYKAL_NOJ [KOLYs - (Nw(B.(NwLADIMIROWs; (Na(B.(NlAGUTINs ((NmOSKWAs (NmUZYKAs, 1984)
(NtRI ILI ^ETYRE GODA NAZAD WY WPERWYE PERESTUPILI POROG MUZYKAL_NOJ [KOLY(B.s
Keywords: (NISTORIQs